PENGARUH PAPARAN MEDAN LISTRIK TERHADAP PERKECAMBAHAN PAKCOY (Brassica rapa L.) - Sandya Olga Bitin Vong; Gede Arya Wiguna; Welsiliana Welsiliana (Partner, 2023)
Pakcoy (B. rapa L.) is a plant originating from Tiongkok (China) and East Asia. In improving the quality of pakcoy plants it is necessary to conduct studies to increase the productivity of pakcoy plants namely by using exposure to an electric field. This study aims to determine the effect of electric field exposure on pakcoy germination. The electric field used is an electric field with a frequency of 1.0 kHz. Variations in the magnitude of the electric field used are 1.15, 1.38 and 1.62 kV/m. The results showed that exposure to the electric field on the pakcoy plants produced better pakcoy sprouts than the control. Treatment of exposure to an electric field of 1.62 kV/m resulted in the most optimum germination power, germination rate, average germination time and vigor index with respective values (100) %, (5.14) %/etmal, (0.88) Day and (100) %. Increased germination, germination rate, average germination time and vigor index are expected to increase pakcoy production.Keywords: Electric Field, Pakcoy Seed, Growth